2018
DOI: 10.1016/j.bbadis.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded rhodopsin mutants display variable aggregation properties

Abstract: The largest class of rhodopsin mutations causing autosomal dominant retinitis pigmentosa (adRP) is mutations that lead to misfolding and aggregation of the receptor. The misfolding mutants have been characterized biochemically, and categorized as either partial or complete misfolding mutants. This classification is incomplete and does not provide sufficient information to fully understand the disease pathogenesis and evaluate therapeutic strategies. A Förster resonance energy transfer (FRET) method was utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
(79 reference statements)
2
30
0
Order By: Relevance
“…Interestingly, no effects on oligomer formation were observed in the cells regenerated with 9-cis-retinal prior to the treatment with flavonoids, thus supporting other results indicating that flavonoids bind to and modulate the properties of the ligand-free opsin only. Moreover, the flavonoid-stimulated increased BRET signal occurred due to the formation of opsin oligomers rather than aggregates as they were disrupted with the DDM detergent, in opposition to the RP-linked opsin aggregates that are not sensitive to such treatment (59). Thus, this finding suggests that increased opsin stability could be related to the formation of tightly packed oligomers within the biological membranes.…”
Section: Effects Of Flavonoids On Rhodopsin Propertiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, no effects on oligomer formation were observed in the cells regenerated with 9-cis-retinal prior to the treatment with flavonoids, thus supporting other results indicating that flavonoids bind to and modulate the properties of the ligand-free opsin only. Moreover, the flavonoid-stimulated increased BRET signal occurred due to the formation of opsin oligomers rather than aggregates as they were disrupted with the DDM detergent, in opposition to the RP-linked opsin aggregates that are not sensitive to such treatment (59). Thus, this finding suggests that increased opsin stability could be related to the formation of tightly packed oligomers within the biological membranes.…”
Section: Effects Of Flavonoids On Rhodopsin Propertiesmentioning
confidence: 89%
“…Cells were resuspended and transferred from the 96-well cell culture plate to a white-walled opaque 96-well plate (Corning Life Sciences). DDM in PBS at a final concentration of 5 or 0.1 mM was added to the wells (59). Coelenterazine h was diluted to 25 M in PBS from a 2.5 mM stock solution.…”
Section: Bret Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, RHO mutants can recruit WT RHO into intracellular aggregates (62)(63)(64). In contrast to that, recent studies suggest that in mammalian cells, misfolded RHO P23H does not aggregate with properly folded RHO WT (65,66), although other evidence does suggest there is a dominant-negative effect of RHO P23H on the WT protein (2, 67).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these in vitro studies suggested the pharmacological potential of cis-retinoids. However as discovered recently, 9-cis-retinal added to the cells co-expressing adRP mutants together with WT opsin resulted in the aggregation of the mutant receptor, indicating that treatment with this pharmacological chaperone could be beneficial for the homozygous patient but rather ineffective or detrimental for heterozygous patients [46]. Therefore, screening for safer, non-retinoid small molecules that would stabilize rod opsin and improve its folding is of urgent importance.…”
Section: Retinoids As Pharmacological Chaperones To Treat Retinitis Pmentioning
confidence: 99%